2018
DOI: 10.1042/bst20160277
|View full text |Cite
|
Sign up to set email alerts
|

The FAM83 family of proteins: from pseudo-PLDs to anchors for CK1 isoforms

Abstract: The eight members of the FAM83 (FAMily with sequence similarity 83) family of poorly characterised proteins are only present in vertebrates and are defined by the presence of the conserved DUF1669 domain of unknown function at their N-termini. The DUF1669 domain consists of a conserved phospholipase D (PLD)-like catalytic motif. However, the FAM83 proteins display no PLD catalytic (PLDc) activity, and the pseudo-PLDc motif present in each FAM83 member lacks the crucial elements of the native PLDc motif. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 70 publications
1
45
0
Order By: Relevance
“…Family with sequence similarity 83, member A (FAM83A), also known as bj-tsa-9, is located on chromosome 8q24 and was initially identified as a potential tumor-specific gene using a bioinformatics method (3). It consists of 434 amino acids, including DUF1669, serine-rich, and protein-rich domains (4), and the DUF1669 domain at its N-terminus is thought to be involved in tumor progression (5,6). It has been reported that FAM83A is overexpressed in a variety of human tumors including lung, breast, testicular, and bladder cancers, suggesting that FAM83A may play a carcinogenic role in the development of cancer (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Family with sequence similarity 83, member A (FAM83A), also known as bj-tsa-9, is located on chromosome 8q24 and was initially identified as a potential tumor-specific gene using a bioinformatics method (3). It consists of 434 amino acids, including DUF1669, serine-rich, and protein-rich domains (4), and the DUF1669 domain at its N-terminus is thought to be involved in tumor progression (5,6). It has been reported that FAM83A is overexpressed in a variety of human tumors including lung, breast, testicular, and bladder cancers, suggesting that FAM83A may play a carcinogenic role in the development of cancer (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Historically, CK1 isoforms were thought to be monomeric, unregulated and constitutively active but there is now accumulating evidence that a family of previously uncharacterised proteins, the FAM83 proteins, act as anchors for several of the CK1 isoforms (, -like, , and ) and can alter their subcellular localisation in response to specific stimuli (14,15). The FAM83 family is composed of 8 members, termed FAM83A-H, which share a conserved Nterminal domain of unknown function 1669 (DUF1669), which mediates the interaction with different CK1 isoforms (14).…”
Section: Introductionmentioning
confidence: 99%
“…However, phosphorylation of distinct substrates by CK1a may trigger their translocation from the spindle to the actin network directly or indirectly. Nonetheless, the findings that the FAM83D-CK1a complex acts at the mitotic spindle add to the evidence for intricate subcellular regulation of CK1 isoforms, which are implicated in many cellular processes from Wnt signalling to the regulation of circadian rhythms, by FAM83 proteins [13]. Given the participation of CK1 isoforms in such diverse biological processes, it is perhaps not surprising that some studies have explored and reported on roles for CK1a in the cell division cycle.…”
Section: Discussionmentioning
confidence: 90%
“…We recently reported that the FAM83 family of poorly characterised proteins act as subcellular anchors for CK1 isoforms through the conserved N-terminal domain of unknown function 1669 (DUF1669) [12]. Our findings that FAM83 proteins interact and colocalise with different CK1 isoforms offer the tantalising possibility that FAM83 proteins direct CK1 isoforms to specific subcellular compartments, and in doing so, regulate their substrate availability/ accessibility [13]. In line with this, we have shown that FAM83G [(aka protein associated with SMAD1 (PAWS1)] activates Wnt signalling through its association with CK1a [14].…”
Section: Introductionmentioning
confidence: 78%